Methodology for evidence-based urology——evidence classification and retrieval - WANG Yunyun; QIN Changjiang; TONG Tiejun; MA Bin; CAO Shiyi; ZHANG Chao; REN Xuequn; LI Xiaodong; ZHANG Miao; WENG Hong; WANG Yang; JIN Yinghui; et al. (Yixue xinzhi zazhi)
Evidence is a core element of evidence-based medicine, with diverse classifications and extensive sources. Most of it is based on journals and is commonly found in databases or websites such as PubMed, Web of Science, and CNKI. The number of literatures is countless, which also puts enormous pressure on researchers to consult and read literature. The field of urology is no exception. This article started with analyzing the characteristics of common clinical questions in the field, introduced the four criteria for their screening and two types of structured templates, clarified the definition, categories, identification, and three requirements for the application of the four evidence classification methods, and explained the selection of retrieval resources, construction of retrieval strategies, specific operational steps, and precautions for the retrieval process to develop and use evidence. In addition, combined with artificial intelligence technology, the future development trend of evidence classification and retrieval in the field of evidence-based urology has been clarified, which provided reference for further promoting the development of evidence-based urology.